1883 Wis. Sess. Laws 290, §§ 1-3 - (:unkn) unknown (General Publisher, 1883)
It shall be unlawful for any minor, within this state, to go armed with any pistol or revolver, and it shall be the duty of all sheriffs, constables, or other public police officers, to take from any minor, any pistol or revolver, found in his possession. It shall be unlawful for any dealer in pistols or revolvers, or any other person, to sell, loan, or give any pistol or revolver to any minor in this state. It shall be unlawful for any person in a state of intoxication, to go armed with any pistol or revolver. Any person violating the provisions of this act, shall be punished by imprisonment in the county jail not exceeding six months, or by fine not exceeding one hundred dollars ($100).
--
Keywords: POSSESSION - MINORS